Molecular characterization of apricot (Prunus armeniaca L.) cultivars using cross species SSR amplification with peach primers - Ruthner, Sz.; Pedryc, A.; Kriska, B.; Romero, C.; Badenes M., M. L. (International Journal of Horticultural Science, 2006)
Apricot takes an important place in Hungarian fruit production. Considering morphological characteristics of apricots it was concluded that the genetics background of European cultivars is very limited. Molecular markers and their use for genotyping have revolutionized the identification of cultivars. In a classic apricot breeding program, it is important to be able to establish unique DNA profiles of selections to identify them unambiguously and to determine their genetic relationship. Presently SSR is far the most frequently performed technique for genetic diversity studies. In this study there were used peach and apricot primer pairs from four different sources in order to examine microsatellite polymorphism among cultivars and investigate relationships among them. The possibility of cross species amplification among different Prunus species using SSR primers allowed us to use primers developed in peach to study genetic diversity in apricot. In this work, 90% of the primers used were able to amplify SSRs in apricot and more than half of them were polymorphic. With the 10 primer pairs utilized were proven to be sufficient to set unique fingerprint for several cultivars studied. The obtained dendrogram classified of the 45 cultivars included in this study into two major groups and several subgroups.